2020
DOI: 10.21608/asnj.2020.79450
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Psycho-Educational Program on Depression among Drug Addict Patients at Assiut University Hospital

Abstract: Psycho-educational program which enhanced health behaviors, increased coping skills, give information about what substance abuse is, and its complications on drug addict patients physical and mental health. Aim of the study: Evaluate the effect of psycho-educational program on depression among drug addict patients. Design: Quasi-Experimental pretest posttest controlled design was used. Subjects and method: The studied sample consisted of 100 drug addict patients, 50 were study group & 50 were control group. To… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…This observation aligns with the notion that individuals with low EI may resort to substances to cope with mental and life challenges and when making decisions under peer pressure [29]. These findings corroborate Sayed et al [30], who found that over 50% of experimental and control groups, mainly influenced by peer pressure. Similarly, López et al [31] reported that about two-thirds of both groups used a single type of substance.…”
Section: Discussionsupporting
confidence: 91%
“…This observation aligns with the notion that individuals with low EI may resort to substances to cope with mental and life challenges and when making decisions under peer pressure [29]. These findings corroborate Sayed et al [30], who found that over 50% of experimental and control groups, mainly influenced by peer pressure. Similarly, López et al [31] reported that about two-thirds of both groups used a single type of substance.…”
Section: Discussionsupporting
confidence: 91%